UPAYA MENGURANGI PROKRASTINASI AKADEMIK SISWA KELAS VIII MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT DI SMP NEGERI 11 SAMARINDA TAHUN AJARAN 2025 - Wendy Anggreni; Dwi Nugroho Hidayanto; Muhaimin Abdillah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study is based on the frequent procrastination behavior exhibited by students who are more focused on non-academic areas, such as prioritizing extracurricular activities over academic assignments. In this case, it can also be seen that guidance counselors never provide group counseling services to address student problems, but rather focus on individual counseling services. This study aims to determine the level of academic delay among students before they are provided with group counseling services using self-management techniques, describe the implementation of these services, and analyze efforts to reduce academic delay among eighth-grade students.The type of research used was experimental research with a pre-experimental design, namely a single group pre-test and post-test design with a quantitative approach. The research subjects were determined using non-probability sampling with a purposive sampling technique involving 6 subjects. The results of this study indicate an increase in efforts to reduce procrastination behavior among students, with a pre-test average score of 83.2 and a post-test average score of 102.5. The T-test analysis produced a significance value (two tails) of 0.020 < 0.05, which indicates a difference between the pre-test and post-test scores, as well as an N-Gain score of 71.39% in the effective category. This study concludes that group counseling using self-management techniques is effective in reducing academic procrastination among students.